Validation of EuroSCORE II to predict mortality in post-cardiac surgery patients in East Java tertiary hospital (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND The European system for cardiac operative risk evaluation (EuroSCORE) II is one of the established risk models used to predict mortality after cardiac surgery. However, its application as a mortality predictor for Indonesian adult cardiac surgery is still unknown. This study aimed to examine the validation of EuroSCORE II in predicting the mortality following adult cardiac surgery in Indonesian adults. METHODS This retrospective cohort study collected data from the medical records and the database of the Department of Thoracic Cardiac and Vascular Surgery at Soetomo General Hospital, Surabaya. Data on the EuroSCORE II variables were collected for patients aged >18 years who underwent coronary artery bypass, heart valve, heart tumors, aortic surgeries, or a combination of these surgeries between January 2016 and December 2018. In-hospital mortality prediction was calculated using the online calculator at www.euroscore.org. The calibration of the EuroSCORE II model was conducted using the Hosmer–Lemeshow test, and discrimination analysis was done using receiver operating characteristic (ROC) curves with area under the ROC curve (AUC) calculation. RESULTS A total of 213 patients met the inclusion criteria and were analyzed for this study. Mortality was 8.9%. The predicted and actual mortalities were 1.74% and 8.9%, respectively. The significance (p-value) of the Hosmer–Lemeshow test was 0.55, indicating good calibration. The AUC of ROC curve was 0.85 (95% CI = 0.77–0.92, p<0.001), suggesting good discrimination. CONCLUSIONS EuroSCORE II has a good calibration and discrimination for cardiac surgery in Indonesian adults.